miRNA Genetic Variants Alter Their Secondary Structure and Expression in Patients With RASopathies Syndromes - de Carvalho, Joseane Biso; de Morais, Guilherme Loss; Vieira, Thays Cristine dos Santos; Rabelo, Natana Chaves; Llerena, Juan Clinton; Gonzalez, Sayonara Maria de Carvalho; de Vasconcelos, Ana Tereza Ribeiro (Frontiers in Genetics, 2019)
RASopathies are a group of rare genetic diseases caused by germline mutations in genes involved in the RAS–mitogen-activated protein kinase (RAS-MAPK) pathway. Whole-exome sequencing (WES) is a powerful approach for identifying new variants in coding and noncoding DNA sequences, including miRNAs. miRNAs are fine-tuning negative regulators of gene expression. The presence of variants in miRNAs could lead to malfunctions of regulation, resulting in diseases. Here, we identified 41 variants in mature miRNAs through WES analysis in five patients with clinical diagnoses of RASopathies (Cardiofasciocutaneous syndrome-P1, Noonan with multiple lentigines or LEOPARD syndrome-P2, Noonan syndrome-P3, provisional Costello syndrome-P4 and provisional Neurofibromatosis type 1-P5). The pathways, biological processes and diseases that were over-represented among the target genes of the mature miRNAs harbouring variants included the RAS, MAPK, RAP1, and PIK3-Akt signalling pathways, neuronal differentiation, neurogenesis and nervous system development, congenital cardiac defects (hypertrophic cardiomyopathy, dilated cardiomyopathy and arrhythmogenic right ventricular cardiomyopathy), and the phenotypes and syndromes of RASopathies (Noonan syndrome, Legius syndrome, Costello syndrome, Cafe au lait spots multiple, subaortic stenosis, pulmonary valve stenosis, and LEOPARD syndrome). Furthermore, eight selected variants in nine mature miRNAs (hsa-miR-1304, hsa-miR-146a, hsa-miR-196a2, hsa-miR-499a/hsa-miR-499b, hsa-miR-449b, hsa-miR-548l, hsa-miR-575, and hsa-miR-593) caused alterations in the secondary structure of precursor miRNAs. Consequently, the variants altered the expression pattern of miRNAs. RT-qPCR expression analysis revealed four differentially expressed miRNAs that were downregulated: miRNA-146a-3p in P1, P2, P3, P4 and P5, miR-1304-3p in P2, P3, P4 and P5, miR-196a2-3p in P3, and miR-499b-5p in P1. miR-499a-3p was upregulated in P1, P3 and P5. These results indicate that miRNAs show different expression patterns when these variants are present in patients. Therefore, this study characterized the role of miRNAs harbouring variants related to RASopathies for the first time and indicated the possible implications of these variants for phenotypes of RASopathies such as congenital cardiac defects and cardio-cerebrovascular diseases. The expression and existence of miRNA variants may be used in the study of biomarkers of the RASopathies.